Conciencia ambiental en estudiantes del quinto de secundaria del colegio cooperativo - César Vallejo. Iquitos. Loreto. 2024 - Paima Martinez, Freddy Fabiano (2025)
This research work was developed at the Cesar Vallejo school in Iquitos in 2024, its objective was to determine environmental awareness from the cognitive and behavioral perspective in 5th grade high school students. The research was quantitative in its approach, the data collection planning was prospective, and its level of research is descriptive relational, and its research design is non-experimental, cross-sectional. The research had the participation of 101 enrolled students belonging to three sections, who were present during the application of the data collection instrument. The survey technique was used and a questionnaire was applied, with two indicators, one with 9 questions and the other with 10 statements on the Likert type scale that were previously validated in content and subjected to reliability tests. The data obtained were analyzed based on the objectives and hypotheses of the research and were organized in a Basic Data Matrix (BDM), to then be processed and analyzed. The main findings showed a predominance of average levels of cognitive environmental awareness; most students had average levels of cognitive environmental awareness. Furthermore, favorable attitudes toward environmental behaviors predominated, indicating a strong behavioral predisposition toward environmental sustainability. Cognitive environmental awareness and behavioral environmental awareness can develop independently in educational contexts, which is consistent with recent studies showing a weak or nonexistent correlation between environmental knowledge and pro-environmental behavior.